Pediatric hearing thresholds post-bacterial meningitis (2020)
Introduction: Disabling hearing loss as a sequela of bacterial meningitis results from damage to the auditory system. This study was designed to ascertain the hearing thresholds in survivors of bacterial meningitis and the risk factors of hearing loss in childhood bacterial meningitis. Methodology: One hundred and two children admitted and treated for bacterial meningitis were recruited prospectively along with 102 age- and sex-matched controls who had auditory evaluation using otoacoustic emission and auditory brain stem response tests 48 h prior to hospital discharge. This was also repeated at the follow-up clinic at 1 month after hospital discharge, irrespective of the initial hearing assessment results. Result: There were 57 (55.9%) males and 45 (44.1%) females among the cases (mean age, 5.34 ± 4.40 years) and 55 (53.9%) males and 47 (46.1%) females among the controls (mean age, 5.31 ± 3.15 years). The prevalence of hearing loss was 30.4% among the cases, while it was 6.9% among the controls. The risk factors of hearing impairment in this study were the presence of anemia, leukocytosis, and hypoglycorrhachia. Conclusion: Hearing impairment with varying degrees of severity is a frequent complication of bacterial meningitis in children